2001
DOI: 10.1038/emm.2001.4
|View full text |Cite
|
Sign up to set email alerts
|

L-ergothioneine level in red blood cells of healthy human males in the Western province of Saudi Arabia

Abstract: Ergothioneine is widely distributed in biological systems, particularly in red blood cells of animals. However, it's functional role in human body is not well understood. In order to investigate the biochemical effect of L-ergothioneine, its concentration changes in human blood with respect to ages in healthy individuals was first investigated. L-ergothioneine concentrations in the blood of Saudi males from western province at different stages of life were measured by the procedure of Carlsson et al., 1974. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
4
24
0
Order By: Relevance
“…The average ERT level (mean ± SD) in real samples was 55.99 ± 49.66 mol/L (females 62.14 ± 57.62; males 49.84 ± 39.76 mol/L) and, on average, our results were consistent with the values reported by other authors for whole blood ERT content [32]. Moreover, as already reported in other studies [33], they show a considerable variation in the SD of ERT concentration, which could reflect the different feeding habits of the healthy subjects.…”
Section: Resultssupporting
confidence: 93%
“…The average ERT level (mean ± SD) in real samples was 55.99 ± 49.66 mol/L (females 62.14 ± 57.62; males 49.84 ± 39.76 mol/L) and, on average, our results were consistent with the values reported by other authors for whole blood ERT content [32]. Moreover, as already reported in other studies [33], they show a considerable variation in the SD of ERT concentration, which could reflect the different feeding habits of the healthy subjects.…”
Section: Resultssupporting
confidence: 93%
“…This was noted in an earlier report on serum zinc levels of individuals in the same area of the country. 20 However, our calculated means in Tables 1 and 3 are higher than the earlier reported means for subjects above one year of age, and close to the mean for the younger subjects. Two factors are likely to cause the noted changes with age; the first is the dietary intake that changes as the infant grows, and the second is the incidence of diarrhea.…”
Section: Discussionsupporting
confidence: 53%
“…Ergothioneine can accumulate to high levels in some human and animal tissues, including red blood cells (with basal levels of~125 lM and~220 lM in human and mouse whole blood, respectively, and millimolar levels reported in red blood cells [52,53]), liver and spleen (with basal levels of~350 lmolÁg À1 tissue and 100 lmolÁg À1 tissue in mouse liver and spleen, respectively) [22,31-33]. Our recent study [33] demonstrated that when ET is orally administered to mice, it accumulates rapidly in the liver and blood cells but also enters most (or perhaps all) other tissues, including brain, heart, lung, kidney, spleen and eye.…”
Section: Ergothioneine In Tissues Extracellular Fluids and Cell Culturementioning
confidence: 99%